1995
DOI: 10.1007/bf02257017
|View full text |Cite
|
Sign up to set email alerts
|

Use of closure area and resources per unit area for assessing undiscovered petroleum resources in part of the Cooper Basin, South Australia

Abstract: Undiscovered petroleum resources may be assessed using a computer program that simulates drilling each trap in a play end estimates the size of each potential discovery by multiplying together estimates of area of closure (Ad.,) and resources per unit area (V~). There are several ways of determining values for A~ and VA so that the method can be widely applied. As an example, the sales gas potential of pert of the Cooper Basin in South Australia is assessed using statistical projections of Ioglinear models to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studies of raised beaches concentrating on Novaya Zemlya (Forman et al, 1995(Forman et al, , 2004Zeeberg et al, 2001) reported only moderate uplift of maximally 20 m during the Holocene. This implies that isostatic rebound of the Kara Sea coast is less than eustatic rise and the maximum thickness of any ice on the shelf and adjacent coastal plain is unlikely to have exceeded about 500 m (Lambeck, 1995;Lambeck, 1996;Svendsen et al, 2004).…”
Section: Previous Investigations and Sea Level Historymentioning
confidence: 96%
“…Studies of raised beaches concentrating on Novaya Zemlya (Forman et al, 1995(Forman et al, , 2004Zeeberg et al, 2001) reported only moderate uplift of maximally 20 m during the Holocene. This implies that isostatic rebound of the Kara Sea coast is less than eustatic rise and the maximum thickness of any ice on the shelf and adjacent coastal plain is unlikely to have exceeded about 500 m (Lambeck, 1995;Lambeck, 1996;Svendsen et al, 2004).…”
Section: Previous Investigations and Sea Level Historymentioning
confidence: 96%